Health Security in Emergency Medical Services: Bridging X-Ray Technology, Nursing, and Dentistry for Comprehensive Crisis Management - Musa Mohammed Ahmad Daghas,; Khalid Mohammed Eissa Moafa,; Mujali Ali Abushamlah Abdullah Kariri,; Yehia Gassim Mohammed Abu Tawil,; Jibril Ahmed Jibril Jaefer,; Zahra Ibrahim Adhim,; Waleed Mohammed Alahmadi,; Sultan Makki Ali Sumayli,; Mujahed Falah Alkhudari,; Hassan Abdullah Mohammed Asiri, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Health security in Emergency Medical Services (EMS) is critical to the success of any healthcare system, especially during times of crisis or disaster. The integration of X-ray technology, nursing, and dentistry within EMS is pivotal in ensuring a coordinated and effective response. This manuscript explores the role each discipline plays in crisis management, focusing on how their integration can enhance patient outcomes, improve efficiency, and bolster health security. By analyzing interdisciplinary collaboration in emergency situations, this paper demonstrates how a holistic approach can mitigate risks, optimize care, and address the complex needs of patients during medical emergencies.